POTENSI PEMANFAATAN LAHAN TIDUR DI KABUPATEN KERINCI - Karim, M; Adelia, Ismi (Pusat Penelitian dan Pegabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2018)
Abstract: Abstract: Land in Kerinci is still classified as fertile and productive to be processed into farming activities. The purpose of this study was to find out the potential utilization of sleeping land in Koto Tuo Ujung Pasir Village, Lake Kerinci Subdistrict, Kerinci Regency and find out suitable agricultural processing solutions for sleeping land in Koto Tuo Ujung Pasir Village, Lake Kerinci District, Kerinci Regency. This research belongs to the type of quantitative research. Research subjects included: farmers and community members around the sleeping area. The sampling technique used in this study was purposive sampling. Researchers used interactive models from Miles and Huberman in analyzing data. Utilization of sleeping land potential can illustrate the following conditions: 1) internal factors indicate the availability of skilled and experienced workforce to process land, whereas in external factors sales are obtained in addition to farmers' income which is supported by the desired yield of consumers; 2) creating markets and increasing product development on available land by cultivating more productive types of short-term crops; and 3) the prospect of exploiting the potential of sleeping land has a long-term advantage as a market transaction that results in the circulation of money in the community.